Microscopic analysis of ovarian stages of the western king prawn Penaeus (Melicertus) latisulcatus Kishinouye 1896. Issue 1 (2nd January 2021) - Hackett, Nadine; Dixon, Cameron; Dittmann, Sabine; Roberts, Shane; Hooper, Graham; Bolton, Toby
ABSTRACT: The determination of ovarian stages is essential for an understanding of reproductive biology and informing sustainable management of commercially caught marine organisms. This research developed improved microscopic assessment criteria for the prawn, Penaeus (Melicertus) latisulcatus, by reviewing microscopic criteria used in the literature and assessing cell composition of ovary tissue from 97 females. Whilst histological staging is not a new technique, this research outlines new development criteria for assessing ovary development stages in P. latisulcatus . A principal component analysis (PCA) was used with the microscopic classification system and showed distinct groups for each stage. Based on the proportion of cell types, distinct groupings were apparent, which corresponded to the main microscopic stages, in particular for stage 3 ovaries. This revised classification will improve the accuracy of ovarian staging techniques for P. latisulcatus and can be used as a guide for the interpretation and analysis of macroscopic stages during seasonal spawning events for the purpose of better informing fisheries management.